Tradisi Menging di Desa Adat Bangkah Sebagai Ritual Penyucian yang Memperkuat Solidaritas Sosial dan Identitas Religius Masyarakat Bali Aga - Nyoman Nadiana; I Made Ariasa Giri; I Made Sedana (Kamaya: Jurnal Ilmu Agama, 2026)
The Menging Tradition is a local Hindu ritual practiced by the people of Bangkah Traditional Village, Pacung Village, Tejakula District, Buleleng Regency. This article aims to examine the religious, customary, and cosmological foundations of the Menging Tradition, describe its ritual sequence, and analyze its implications for the social, cultural, and religious life of the Bali Aga community. This study employs a qualitative descriptive-interpretative method. Field data were collected through observation, documentation, literature study, and interviews with nine key informants representing customary leaders, ritual priests, village elders, ordinary villagers, women involved in ritual offerings, youth, and pecalang. The data were analyzed through reduction, display, and conclusion drawing. The findings show that the Menging Tradition is grounded in the community’s belief in maintaining the purity of the village and the balance between sekala and niskala. Its implementation includes customary deliberation, preparation of ritual offerings, village purification, collective prayer, observance of customary prohibitions, and closing rites. The tradition strengthens social solidarity through collective participation, preserves Bali Aga cultural identity through the transmission of ancestral values, and deepens religious awareness through self-control, silence, and devotion. Its ecological dimension is reflected in the prohibition of animal slaughter, the avoidance of bloodshed, and the maintenance of village purity during the sacred period. Thus, Menging is not merely an inherited ritual, but a living religious-cultural practice that integrates sacred discipline, communal solidarity, and local wisdom.